Wine in the care of the sick in Portugal from 1701 to 1800 - Cristina Rosa Soares Lavareda Baixinho; Isabel Ferraz Pereira; Óscar Ramos Ferreira; Helga Rafael Henriques (Universidad de Alicante, 2019)
This study aimed to identify the therapeutic use of wine, in the period between 1701 and 1800, in Portugal, and characterize the nursing care in the preparation and administration of this therapy. The historical method was used. Data collection was done by consulting the primary sources in libraries, with especial emphasis on the library of the Royal Palace of Mafra. The ethical procedures of historical research were taken into account. Wine has been present in the life of man since its earliest days. It was an important element of life and festivities, but also a therapeutic element for the cure of diseases and preparation for eternity. During the eighteenth century it was widely used as a therapy for the treatment of different diseases, including aesthetic treatments. These preparations were carried out in the Boticas, and the nurses were in charge of its administration, as well as in charge of preparing the baths, sheets and cloths of herbs for the application of this medication. Therapy by wine was prescribed by the physician, prepared in the public pharmacies, or in the convents' nurseries, and administered by the nurses, who ensured the effectiveness of the treatment.